Warm mix asphalt mixture capable of reducing construction temperature and preparation method thereof

By using a composite warm mixer in the warm-mixed asphalt mixture, cracked wax and pyrolyzed oil reduce the viscosity of the matrix asphalt, the problem of reduced fluidity of warm-mixed asphalt in a low temperature environment is solved, and the strength and construction efficiency of the asphalt pavement are improved.

CN116573885BActive Publication Date: 2025-04-08SHANDONG LUQIAO CONSTR
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310379233.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-04-08
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

In low temperature environments, the fluidity of the warm-mixed asphalt mixture decreases, resulting in voids appearing in the asphalt pavement, thereby reducing the strength of the asphalt pavement and increasing the construction difficulty.

Method used

A composite warm mixer is used, which consists of a cracking product, a modifier and a heat storage powder. The cracking wax formed by thermal cracking of waste rubber and plastic is combined with the pyrolytic oil and the matrix asphalt to form a micelle structure, reducing the viscosity of the matrix asphalt and improving fluidity.

Benefits of technology

In low temperature environments, the fluidity loss rate of warm-mixed asphalt mixture slows down, reducing construction difficulty, and increasing the strength of the asphalt pavement by filling voids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004171515000000051
    Figure BDA0004171515000000051
  • Figure BDA0004171515000000061
    Figure BDA0004171515000000061
  • Figure BDA0004171515000000071
    Figure BDA0004171515000000071
Patent Text Reader

Abstract

The present application relates to the technical field of asphalt mixtures, and specifically discloses a warm-mix asphalt mixture that can reduce the construction temperature and a preparation method thereof. The warm-mix asphalt mixture includes the following raw materials in parts by weight: 80-120 parts of base asphalt; 1200-2050 parts of coarse aggregate; 380-820 parts of fine aggregate; 80-160 parts of mineral powder; 1.8-7.2 parts of composite warm-mix agent; the raw materials for preparing the composite warm-mix agent include cracking products, modifiers and heat storage powder; the weight ratio of cracking products, modifiers and heat storage powder is (10-20):2:(1-2). The preparation method thereof is: S1, base asphalt and composite warm-mix agent are used to prepare coated asphalt; S2, coarse aggregate, fine aggregate, mineral powder and coated asphalt are mixed to obtain warm-mix asphalt mixture. The present application has the effect of reducing the construction difficulty of warm-mix asphalt in a low temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of asphalt mixture technology, and in particular to a warm mix asphalt mixture capable of reducing construction temperature and a preparation method thereof. Background Art

[0002] Asphalt pavement refers to various types of pavement paved with road asphalt mixture mixed with mineral materials. At present, the most widely used asphalt pavement is mainly paved with ordinary hot mix asphalt (HMA). However, in the production process of HMA, asphalt (or modified asphalt) and aggregates need to be heated to 160-180℃, and the temperature of mixing, paving and rolling should not be lower than 140℃. This process consumes a lot of fuel and releases a lot of harmful gases during construction.

[0003] Warm mix asphalt is an asphalt mixture with a mixing temperature 20-30℃ lower than that of hot mix asphalt, and its performance is equal to or close to that of hot mix asphalt. Warm mix asphalt technology reduces the production temperature of asphalt mixture, saves energy consumption, and reduces harmful gas emissions.

[0004] During winter construction in northern regions, the maximum temperature is below 10°C, and the fluidity of warm-mix asphalt is reduced during paving and rolling, resulting in gaps in the asphalt pavement, which in turn reduces the strength of the asphalt pavement. In order to ensure the quality of the asphalt pavement, the construction process needs to be accelerated, and the difficulty of warm-mix asphalt pavement construction increases. Summary of the invention

[0005] In order to reduce the construction difficulty of warm mix asphalt in a low temperature environment, the present application provides a warm mix asphalt mixture and a preparation method thereof that can reduce the construction temperature.

[0006] In the first aspect, the present application provides a warm mix asphalt mixture that can reduce the construction temperature, which adopts the following technical solution:

[0007] The warm-mix asphalt mixture capable of reducing the construction temperature comprises the following raw materials in parts by weight: 60-120 parts of base asphalt; 80-120 parts of base asphalt; 1200-2050 parts of coarse aggregate; 380-820 parts of fine aggregate; 80-160 parts of mineral powder; and 1.8-7.2 parts of a composite warm-mix agent. The raw materials for preparing the composite warm-mix agent comprise cracking products, a modifier and heat storage powder, the raw materials for preparing the cracking products comprise waste rubber and plastic and a cracking catalyst, the weight ratio of the waste rubber and plastic to the cracking catalyst being (60-100):3; the weight ratio of the cracking products, the modifier and the heat storage powder being (10-20):2:(1-2).

[0008] By adopting the above technical scheme, waste rubber and plastic are pyrolyzed to form pyrolysis gas, pyrolysis oil, pyrolysis wax and heavy pyrolysis liquid and other pyrolysis products. In the preparation process of warm-mix asphalt mixture, melted pyrolysis wax and pyrolysis oil are combined with base asphalt. Pyrolysis oil increases the oil content in asphalt. Melted pyrolysis wax is adsorbed on the surface of asphalt to form a lubricating film, which reduces the viscosity of asphalt. When constructed at low temperature, the rate of fluidity loss of warm-mix asphalt mixture slows down, reducing the construction difficulty of warm-mix asphalt in low temperature environment. After the construction of warm-mix asphalt mixture is completed, the base asphalt begins to solidify, and part of the pyrolysis liquid, pyrolysis oil and pyrolysis wax fill the gaps between the warm-mix asphalt mixture, which increases the strength of the warm-mix asphalt pavement and reduces the construction difficulty of warm-mix asphalt in low temperature environment.

[0009] Optionally, the preparation steps of the modifier include: after evenly mixing polyacrylamide and part of propanol, adding a grafting catalyst, stirring in an oil bath and heating to 60°C to obtain a reserve solution; after evenly mixing a lipophilic alkyl halide and the remaining propanol, dripping into the reserve solution, heating the oil bath to 90°C, reflux reaction for 6 hours, and cooling to obtain a mixed solution; centrifuging the mixed solution, removing propanol from the supernatant, and obtaining a modifier.

[0010] By adopting the above technical scheme, the lipophilic alkyl halide and polyacrylamide are reacted and grafted to generate an amphiphilic modifier, the lipophilic property of the modifier is provided by the lipophilic alkyl halide, and the pyrolysis oil in the cracking product is well compatible. The modifier cooperates with the cracking product, the cracking oil in the cracking product carries the modifier and the oil of the base asphalt is miscible, the melted cracking wax is adsorbed on the asphaltene surface of the base asphalt, and the hydrophilic part of the modifier surrounds the base asphalt, and finally forms a micellar structure from outside to inside, which is a structural water film, a hydrophilic part of the modifier and a mixture of cracking wax, a lipophilic part of the modifier and a mixture of base asphalt and cracking products. When the warm-mix asphalt mixture is constructed under a low temperature environment, the structural water film, cracking wax and cracking oil work synergistically to reduce the viscosity of the base asphalt, slow down the loss rate of the fluidity of the warm-mix asphalt mixture, and reduce the construction difficulty of the warm-mix asphalt under a low temperature environment.

[0011] Optionally, the lipophilic alkyl halide is 4-methylbenzyl bromide.

[0012] By adopting the above technical scheme, the melting point of 4-methylbenzyl bromide is 34-36°C, and the melting point of the modifier obtained by grafting 4-methylbenzyl bromide with polyacrylamide is lowered. During the compaction process of warm-mix asphalt mixture, the residual fluidity of the pyrolysis product modified by the modifier fills the voids of the warm-mix asphalt mixture, thereby increasing the density of the warm-mix asphalt mixture and thus increasing the strength of the warm-mix asphalt mixture.

[0013] Optionally, the weight ratio of 4-methylbenzyl bromide to polyacrylamide is (4-20):1.

[0014] By adopting the above technical scheme and the above weight ratio, the interfacial activity of the modifier prepared by 4-methylbenzyl bromide and polyacrylamide is relatively high, which reduces the surface tension between the modifier and the oil agent, facilitates the mutual dissolution of the modifier and the cracking oil, and the modifier and the oil component of the base asphalt, thereby improving the stability of the micelles, thereby improving the viscosity reduction effect of the base asphalt, and facilitating the construction of warm-mix asphalt mixtures in low temperature environments.

[0015] Optionally, the grafting catalyst is potassium carbonate.

[0016] By adopting the above technical solution, potassium carbonate is used as a catalyst to improve the grafting efficiency of 4-methylbenzyl bromide and polyacrylamide, and the water absorption of potassium carbonate reduces the agglomeration of polyacrylamide during the grafting reaction, thereby improving the synthesis efficiency of the modifier.

[0017] Optionally, the cracking catalyst is an Fe-based clay catalyst.

[0018] By adopting the above technical solution, the Fe-based clay catalyst has a high specific surface area, the active center Fe2O3 is better dispersed on the carrier, and the catalytic activity for waste rubber and plastic is high.

[0019] Optionally, the heat storage powder is powdered rigid polyurethane.

[0020] By adopting the above technical solution, the powdered rigid polyurethane is evenly dispersed in the cracking product, and the oil resistance of the rigid polyurethane makes it difficult to decompose in the cracking product. The powdered rigid polyurethane is mixed with the cracking wax and the base asphalt, and its low thermal conductivity reduces the temperature loss rate of the warm mix asphalt mixture and reduces the construction difficulty of the warm mix asphalt in a low temperature environment.

[0021] Optionally, the waste rubber and plastic preparation step includes: mixing waste rubber and waste plastic and then shearing them to obtain waste rubber and plastic.

[0022] By adopting the above technical solution, the use of waste rubber and waste plastic is in line with the concept of environmental protection. The waste rubber and plastic obtained by mixing waste rubber and waste plastic, the pyrolysis oil and cracking wax produced during the cracking process are used together to reduce the viscosity of the base asphalt, thereby reducing the construction difficulty of warm mix asphalt in a low temperature environment.

[0023] In the second aspect, the preparation method of warm mix asphalt mixture that can reduce the construction temperature provided by the present application adopts the following technical scheme:

[0024] The method for preparing a warm-mix asphalt mixture capable of reducing the construction temperature comprises the following steps:

[0025] S1. Heat the base asphalt, add the composite warm mix agent, and stir evenly at a constant temperature to obtain the coated asphalt;

[0026] S2. Mix the coarse aggregate, fine aggregate, mineral powder and coated asphalt, and mix at a constant temperature of 150° C. to obtain a warm mix asphalt mixture.

[0027] By adopting the above technical solution, the composite warm mix agent is fully in contact with the base asphalt to obtain the coated asphalt, which has a lower viscosity than the base asphalt, and the warm mix asphalt mixture is not easy to solidify during construction in a low temperature environment. Mixing the warm mix asphalt mixture at 150℃ saves energy and reduces the emission of harmful substances.

[0028] Optionally, in S1, the base asphalt is heated to 90-100°C and the stirring speed is 800-1000rpm.

[0029] By adopting the above technical solution, low-speed stirring is used to evenly mix the base asphalt and the composite warm mix agent; the temperature of the base asphalt and the composite warm mix asphalt when mixed is 90-100°C, which reduces the probability of oil overflow due to excessive temperature of the coated asphalt.

[0030] In summary, the present application includes at least one of the following beneficial technical effects:

[0031] 1. After the composite warm mix agent is mixed with the base asphalt, a micellar structure is formed, which is composed of a structural water film, a mixture of the hydrophilic part of the modifier and the cracked wax, and a mixture of the lipophilic part of the modifier and the base asphalt and the cracked product. When the warm mix asphalt mixture is constructed under low temperature, the structural water film, the cracked wax and the cracked oil work together to reduce the viscosity of the base asphalt, slow down the loss of fluidity of the warm mix asphalt mixture, and reduce the construction difficulty of the warm mix asphalt under low temperature environment;

[0032] 2. Waste rubber and waste plastic are both high molecular polymers and can be thermally cracked into small molecules. Waste rubber can be thermally cracked into pyrolysis gas, pyrolysis oil and heavy pyrolysis liquid, and plastic can be thermally cracked into wax and pyrolysis oil. After the waste rubber and waste plastic are mixed, the pyrolysis oil, pyrolysis wax and heavy pyrolysis liquid are used in combination with the base asphalt to reduce the viscosity of the base asphalt, thereby improving the fluidity of the asphalt. When constructing in a low temperature environment, warm mix asphalt is not easy to solidify, thereby reducing the construction difficulty of warm mix asphalt in a low temperature environment;

[0033] The interfacial activity of the modifier prepared from 3.4-methylbenzyl bromide and polyacrylamide is high, which reduces the surface tension between the modifier and the oil agent, facilitates the mutual solubility of the modifier and the cracking oil, and the modifier and the oil component of the base asphalt, thereby improving the stability of the micelles, and further improving the viscosity reduction effect on the base asphalt, which facilitates the construction of warm mix asphalt mixtures in low temperature environments. DETAILED DESCRIPTION

[0034] The present application is further described in detail below with reference to examples and comparative examples.

[0035] In the following examples, if no specific conditions are specified, the reaction was carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0036] The asphalt is 70# road petroleum asphalt;

[0037] The coarse aggregate is crushed stone with a particle size of 6-12cm and an apparent relative density of 2.7-2.9g / cm 3 ;

[0038] Fine aggregate gravel, particle size is 20 mesh, apparent relative density is 2.889g / cm 3 ;

[0039] The particle size of the mineral powder is 400 mesh and the water content is less than or equal to 1.0.

[0040] Preparation Example

[0041] Preparation Example 1

[0042] S1, waste rubber and waste plastic are mixed in a weight ratio of 1:1, the mixture is sheared into block-shaped waste rubber and plastic with a particle size of less than 5 cm, 100 kg of waste rubber and plastic and 3 kg of Fe clay catalyst are put into a cracking reactor, nitrogen is purged for about 5 minutes to exhaust the air in the reactor, and then the cracking reactor is closed;

[0043] S2, turn on the stirring device, adjust the motor speed to 100-120r / min, raise the temperature to 260°C under the protection of inert gas N2, and continue to crack at this temperature for 30 minutes;

[0044] S3, after the temperature in the kettle drops to room temperature, open the vent valve to discharge the waste gas generated during the cracking process, and finally take out the cracking product;

[0045] S4, magnetically stirring 6 kg of 4-methylbenzyl bromide and 8 L of propanol for 30 min to fully disperse the 4-methylbenzyl bromide to obtain a propanol solution of 4-methylbenzyl bromide;

[0046] S5, 0.3 kg of polyacrylamide was mixed with 8 L of propanol, and magnetic stirring was used for 30 min to fully disperse the polyacrylamide, 0.4 kg of potassium carbonate was added, and the mixture was stirred in an oil bath and heated to 60° C. to obtain a standby solution;

[0047] S6, using a peristaltic pump to dropwise add the propanol solution of 4-methylbenzyl bromide prepared in S4 into the reserve solution at a dropping speed of 5 ml / min. After all the solutions have been dropped, the temperature of the oil bath is raised to 90° C., refluxed for 6 h, the oil bath heating is turned off, and the temperature of the oil bath pot is cooled to room temperature to obtain a mixed solution;

[0048] S7, centrifuging the mixed solution at a speed of 9500 r / min, and subjecting the supernatant to rotary evaporation at 60° C. for 6 h to completely evaporate the solvent propanol to obtain a modifier;

[0049] S8. Take 90 kg of the pyrolysis product prepared in S3 and mix it with 9 kg of the modifier prepared in S7, and stir it at 70° C. for 30 min to obtain a composite warm-mix agent.

[0050] Preparation Example 2-Preparation Example 15

[0051] The difference from Preparation Example 1 is that the amount of each material added is different, see Table 1 for details:

[0052] Table 1 Raw materials of preparation example

[0053]

[0054] Example

[0055] Example 1

[0056] S1. Heat 80 kg of base asphalt to 90° C., add 1.8 kg of the composite warm mix agent prepared in Preparation Example 1, and stir at a constant temperature for 25-30 min at a stirring speed of 1000 rpm to obtain coated asphalt;

[0057] S2. 1200 kg of coarse aggregate and 380 kg of fine aggregate are mixed and preheated to 110° C., and then put into coated asphalt with 80 kg of mineral powder, heated to 150° C., and mixed at a constant temperature to obtain a warm mix asphalt mixture.

[0058] Example 2-Example 13

[0059] The difference from Example 1 is that the amount of each material added is different, see Table 2 for details:

[0060] Table 2 Raw materials of Example 1-Example 13 (kg)

[0061]

[0062] Example 14-Example 15

[0063] The difference from Example 2 is that the stirring speed and asphalt heating temperature in S1 are different, see Table 4 for details:

[0064] Table 4 Reaction conditions of Example 2 and Comparative Examples 7-10

[0065] Stirring speed / rpm Asphalt heating temperature / ℃ Example 2 1000 90 Embodiment 14 1000 100 Embodiment 15 800 90

[0066] Comparative Example

[0067] Comparative Example 1-Comparative Example 6

[0068] The difference from Example 2 is that the addition amount of each material is different, wherein in Comparative Example 2, ordinary commercially available Sasobit warm mix agent is added to replace the composite warm mix agent, as shown in Table 3:

[0069] Table 3 Raw materials of Example 2 and Comparative Examples 1 to 6 (kg)

[0070]

[0071] Comparative Example 7-Comparative Example 10

[0072] The difference from Example 2 is that the stirring speed and asphalt heating temperature in S1 are different, see Table 4 for details:

[0073] Table 4 Reaction conditions of Example 2 and Comparative Examples 7-10

[0074] Stirring speed / rpm Asphalt heating temperature / ℃ Example 2 1000 90 Comparative Example 7 1000 80 Comparative Example 8 1000 150 Comparative Example 9 600 90 Comparative Example 10 2000 90

[0075] Performance testing

[0076] Test methods

[0077] 1. The maximum bending strain (με) of the warm-mix asphalt mixture specimen at failure was measured by the method in T0715-2011 asphalt mixture bending test in JTG E20-2011 Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering. After the warm-mix asphalt mixture was heated to 110°C, the sample was prepared. The ambient temperature during sample preparation was 5°C and the test temperature was 5°C. The test results are detailed in Table 5.

[0078] 2. The void ratio (%) of asphalt mixture is measured by the method in T0705-2011 Density test of compacted asphalt mixture (surface dry method) in "JTG E20-2011 Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering", so as to calculate the void change rate (%). The calculation method of void change rate (%) is as follows:

[0079] Void change rate (%) = (VV1-VV2) / VV2×100

[0080] VV1 (%) - After the warm mix asphalt mixture is heated to 110°C, the sample is made. The ambient temperature during the sample making is 5°C.

[0081] The sample was left to stand for 2 hours in a 5°C environment before testing, and the void ratio was obtained;

[0082] VV2 (%) - After the warm mix asphalt mixture is heated to 110°C, the sample is made. The ambient temperature during the sample making is 25°C.

[0083] The sample was left to stand for 2 hours in a 25°C environment before testing, and the void ratio was obtained;

[0084] Note: The void ratio calculation retains two decimal places. The test results are detailed in Table 5.

[0085] Table 5 Test results of various embodiments and comparative examples

[0086]

[0087] During the sample preparation process, the warm-mix asphalt mixture gradually solidifies. During this process, pressure is applied to shape the sample, and the unsolidified raw materials flow into the sample gaps, thereby filling the sample gaps until the warm-mix asphalt no longer flows under this pressure. Therefore, the void ratio of the test sample can be used to infer the fluidity loss rate of the warm-mix asphalt mixture under this experimental environment. In summary, the void change rate measured under the 25℃ construction environment and the 5℃ construction environment can be used to evaluate the effect of the composite warm-mix agent in delaying the fluidity loss of the warm-mix asphalt mixture under low temperature conditions.

[0088] In combination with Example 1, Example 2 and Example 3 and Table 5, by adjusting the addition amount and type of base asphalt, coarse aggregate, fine aggregate, mineral powder and composite warm mix agent, the fluidity loss of warm mix asphalt in a low temperature environment is reduced, the mechanical properties of the warm mix asphalt mixture after construction at low temperature are improved, and the construction difficulty of the warm mix asphalt mixture in a low temperature environment is reduced.

[0089] Combining Example 2 and Comparative Example 1 with Table 5, it can be seen that the addition of the composite warm mix agent effectively reduces the void change rate of the warm mix asphalt mixture and increases the maximum flexural tensile strain at failure.

[0090] Combining Example 2, Comparative Example 1 and Comparative Example 2 and Table 5, it can be seen that compared with the use of conventional Sasobit warm mix agent, the use of composite warm mix agent reduces the void change rate of warm mix asphalt mixture and increases the maximum flexural strain at failure.

[0091] In combination with Example 2, Example 4-Example 11 and Table 5, by replacing different types of composite warm mix agents, the fluidity loss of warm mix asphalt in a low temperature environment is reduced, the mechanical properties of the warm mix asphalt mixture after construction at low temperature are improved, and the construction difficulty of the warm mix asphalt mixture in a low temperature environment is reduced.

[0092] Combining Example 2, Example 6 and Example 7 and Table 5, it can be seen that with the decrease in the ratio of waste rubber and plastic to Fe-based clay catalyst, the void change of warm-mix asphalt mixture first decreases and then increases, and the maximum bending-tensile strain at failure first increases and then decreases. With the increase in the amount of Fe-based clay catalyst added, the efficiency of waste rubber and plastic cracking is improved, the content of cracking wax and cracking oil in the cracking product is increased, the coating effect of the composite warm-mix agent on the matrix asphalt is improved, the fluidity loss rate of the warm-mix asphalt mixture is reduced, the void change rate is reduced, and the maximum bending-tensile strain at failure increases. With the continuous increase of Fe-based clay catalyst, the Fe-based clay catalyst that does not participate in the cracking reaction provides an alkaline environment for the composite warm-mix agent, the effect of the modifier is weakened, the effect of the composite warm-mix agent on the matrix asphalt is weakened, the void change rate of the warm-mix asphalt mixture increases, and the maximum bending-tensile strain at failure is reduced.

[0093] Combining Example 2 and Comparative Example 3 with Table 5, it can be seen that the addition of the modifier effectively reduces the void change rate of the warm mix asphalt mixture and increases the maximum flexural strain at failure.

[0094] Combining Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 and Table 5, it can be seen that the addition of 4-methylbenzyl bromide alone or polyacrylamide alone to the modifier has little effect on the void change rate and the maximum bending tensile stress at failure of warm mix asphalt. 4-methylbenzyl bromide and polyacrylamide grafting have a synergistic effect.

[0095] Combining Example 2, Example 8 and Example 9 with Table 5, it can be seen that with the increase of the ratio of 4-methylbenzyl bromide to polyacrylamide in the modifier, the void change of the warm mix asphalt mixture first decreases and then increases, and the maximum flexural strain at failure first increases and then decreases.

[0096] It can be seen from Example 2, Example 10 and Example 11 and Table 5 that as the proportion of the modifier in the composite warm mix agent increases, the void change of the warm mix asphalt mixture first decreases and then increases, and the maximum flexural strain at failure first increases and then decreases. As the proportion of the modifier increases, part of the cracked wax is blocked during the preparation of the warm mix asphalt mixture and cannot contact the base asphalt, which reduces the effect of the composite warm mix agent on the base asphalt.

[0097] It can be seen from Example 2 and Comparative Example 6 and Table 5 that the addition of rigid polyurethane reduces the void change rate of the warm mix asphalt mixture and increases the maximum bending tensile strain at failure.

[0098] It can be seen from Examples 10 to 13 and Table 5 that the increase in the proportion of rigid polyurethane reduces the void change rate of the warm-mix asphalt mixture and increases the maximum bending-tensile strain of the warm-mix asphalt mixture when it is destroyed.

[0099] Combining Example 2, Example 14, Comparative Example 7 and Comparative Example 8 with Table 5, it can be seen that when the matrix asphalt is mixed with the composite warm mix agent, the matrix asphalt is heated to 90-100°C, the matrix asphalt coating effect is good, the matrix asphalt heating temperature is lower than 90°C (taking 80°C as an example), the void change rate of the warm mix asphalt mixture increases, and the maximum bending tensile strain at the time of the warm mix asphalt mixture failure decreases. When the matrix asphalt heating temperature is higher than 100°C (taking 150°C as an example), the void change rate and the maximum bending tensile strain at the time of failure of the warm mix asphalt mixture do not change much.

[0100] It can be seen from Example 2, Example 15, Comparative Example 9 and Comparative Example 10 and Table 5 that when the base asphalt is mixed with the composite warm mix agent, the stirring speed is 800-1000rpm, the base asphalt coating effect is good, the stirring speed is less than 800rpm (taking 600rpm as an example) or greater than 1000rpm (taking 2000rpm as an example), the void change rate of the warm mix asphalt mixture increases, and the maximum flexural strain of the warm mix asphalt mixture when it is destroyed decreases.

[0101] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A warm mix asphalt mixture capable of reducing the construction temperature, characterized in that: The invention comprises the following raw materials in parts by weight: 80-120 parts of matrix asphalt; 1200-2050 parts of coarse aggregate; 380-820 parts of fine aggregate; 80-160 parts of mineral powder; 1.8-7.2 parts of composite warm mix agent; the raw materials for preparing the composite warm mix agent include cracking product, modifier and heat storage powder, the raw materials for preparing the cracking product include waste rubber and plastic and cracking catalyst, and the weight ratio of the waste rubber and plastic to the cracking catalyst is (60-100):3; The weight ratio of the pyrolysis product, the modifier and the heat storage powder is (10-20):2:(1-2); The preparation steps of the modifier include: uniformly mixing polyacrylamide and part of propanol, adding a grafting catalyst, stirring in an oil bath and heating to 60°C to obtain a reserve solution; uniformly mixing a lipophilic alkyl halide and the remaining propanol, dripping into the reserve solution, heating the oil bath to 90°C, reflux reaction for 6 hours, and cooling to obtain a mixed solution; centrifuging the mixed solution, removing propanol from the supernatant, and obtaining a modifier; the lipophilic alkyl halide is 4-methylbenzyl bromide; the weight ratio of 4-methylbenzyl bromide to polyacrylamide is (4-20):1; the grafting catalyst is potassium carbonate; the cracking catalyst is an Fe-based clay catalyst; and the heat storage powder is powdered rigid polyurethane.

2. The warm mix asphalt mixture capable of reducing the construction temperature according to claim 1, characterized in that: The waste rubber and plastic preparation step comprises: mixing waste rubber and waste plastic and then shearing them to obtain waste rubber and plastic.

3. The method for preparing a warm mix asphalt mixture capable of reducing the construction temperature according to any one of claims 1-2, characterized in that: The following steps are involved: S1. Heat the base asphalt, add the composite warm mix agent, and stir evenly at a constant temperature to obtain the coated asphalt; S2. Mix the coarse aggregate, fine aggregate, mineral powder and coated asphalt, and mix at a constant temperature of 150° C. to obtain a warm mix asphalt mixture.

4. The method for preparing warm mix asphalt mixture capable of reducing construction temperature according to claim 3, characterized in that: In S1, the base asphalt is heated to 90-100°C and the stirring speed is 800-1000rpm.

Citation Information

Patent Citations

  • Warm mix polymer modified asphalt mixture and preparation method thereof

    CN106630763A